High temperature superconducting materials based on Graphene / YBCO nanocomposite. (2016) - Colie, Maria; Mihaiescu, Dan; Surdu, Adrian; Trusca, Roxana; Vasile, Bogdan; Istrati, Daniela; Ficai, Anton; Plapcianu, Carmen; Andronescu, Ecaterina
Abstract: New route synthesis of YBCO / graphene composite material is described in the present work. The oxide mixture and graphene were obtained separately and then mixed together by ball milling in the mass ratio graphene: YBCO = 1: 100. The oxide mixture was prepared by modified auto combustion reaction starting from stoichiometric amounts of yttrium acetate and barium and copper nitrates without any other organic compound addition. Graphene materials were prepared by reducing GO (i.e. oxidation of graphite powder by a modified Hummers method) with hidrazine sulphate. The final material resulted by applying the ball-milling method was investigated by XRD, SEM, Raman and HRTEM.